Healthcare Provider’s Perception and Attitude of Medications in Kingdom of Saudi Arabia - Alomi, Yousef Ahmed; Alaskari, Dima Ahmad; Almelf, Malak Mohammad; Badawi, Dima Ali; Alshihri, Abdullah Mohammad (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore Healthcare provider’s perception of medications in Kingdom of Saudi Arabia. Methods: It is a 4-months cross-sectional survey of healthcare professionals and knowledge of medicines. The survey consisted of two-part demographic information and second part forty-nine questions divided into four domains. It included domain one: Primary or essential information about healthcare providers medication, domain two: healthcare professionals information about the drug-related problem, domain three: healthcare professionals information about drug-related cost and domain four: Healthcare providers perception of medications. All type of healthcare professionals included in the study. Medline Plus health information and DailyMed-INH elements information from National Institute of Health United State of America were used. The survey was distributed through social media by using what’s App to more than one thousand healthcare professionals overall Kingdom of Saudi Arabia. The survey was made in an electronic format and it analyzed domain four: Healthcare provider’s perception of medications through survey monkey system. Results: The total responders were (188) Healthcare professionals. Of those 177 (95.16%) were Saudi and 9 (4.84%) were non-Saudi. The gender distribution 120 (63.83%) were females and 68 (36.17%) were males. The most of Healthcare professionals were pharmacists 93 (71.54%), followed by nurses 18 (13.85%) and physicians 15 (11.54%). The responders showed that 60 (32.26%) takes their medication without any prior information, 110 (59.14%) described drug to the person had the same disease and 130 (70.27%) use the medication without a prescription. Also, 65 (35.33%) of responders stopped their medication when they feel better and 116 (63.04%) of them completed entire medication course of therapy. The responders displayed that 119 (63.98%) believed Drug Information given by health care was not enough and 68 (36.56%) of responders thought that their medication knowledge was not enough. Conclusion: To better educate clinicians and pharmacists about medications, some professionals Should be resourced. These resources include information specific to classes of medications and medication types that have high specific potential, as well as suggestions on how to assess function and Counsel Participant’s information and knowledge of Medication’s Perception.
Keywords: Healthcare professional; Knowledge; Ministry of Health; Saudi Arabia; Medications; Perception; Attitudes